Don't stop focusing when it gets harder! The positive effects of focused attention on affective experience at high intensities. Issue 18 (17th September 2022) - Limmeroth, Julia; Schücker, Linda; Hagemann, Norbert
ABSTRACT: Experiencing negative affect during exercise partially explains high levels of physical inactivity. An important direction for research is to better understand how and why interindividual differences in affective experiences occur while exercising. The dual-mode theory suggests that the interaction of cognitive processes and interoceptive cues influence the affective response. Hence, attentional control in form of adopting an external or internal attentional focus could lead to different affective responses depending on intensity. This study examines possible interactions between self-selected running intensities and attentional focus on affect. Fifty-eight inexperienced runners (30.14 ± 9.19 years; 38% female) ran 9 × 3 min outdoors around a large pond. While running at three intensities, they were instructed to focus on their breathing, on the environment, or did not receive an instruction. Dependent measures were affect, heart rate, and speed. The results revealed a significant interaction between attentional focus and intensity on affect ( p = .01, η 2 p  = .08). At subjectively perceived light intensity, participants' affective outcomes benefit from non-focusing attention, whereas during hard intensity the opposite seems helpful: to focus on breathing or to the environment. These findings shed new light on the interaction of focusing attention and running intensity to improve the affective experience.